No bidirectional relationship between depression and periodontitis: A genetic correlation and Mendelian randomization study - Nolde, Michael; Holtfreter, Birte; Kocher, Thomas; Alayash, Zoheir; Reckelkamm, Stefan Lars; Ehmke, Benjamin; Baurecht, Hansjörg; Baumeister, Sebastian-Edgar (Frontiers in immunology, 2022)
Observational and research suggested a bidirectional relationship between depression and periodontitis. We estimated the genetic correlation and examined directionality of causation. The study used summary statistics from published genome wide association studies, with sample sizes ranging from 45,563 to 797,563 individuals of European ancestry. We performed linkage disequilibrium score regression (LDSC) to estimate global correlation and used Heritability Estimation from Summary Statistics (ρ-HESS) to further examine local genetic correlation. Latent Heritable Confounder Mendelian randomization (LHC-MR), Causal Analysis using Summary Effect estimates (CAUSE), and conventional MR approaches assessed bidirectional causation. LDSC observed only weak genetic correlation (r = 0.06, P-Value = 0.619) between depression and periodontitis. Analysis of local genetic correlation using ρ-HESS did not reveal loci of significant local genetic covariance. LHC-MR, CAUSE and conventional MR models provided no support for bidirectional causation between depression and periodontitis, with odds ratios ranging from 1.00 to 1.06 in either direction. Results do not support shared heritability or a causal connection between depression and periodontitis.